Peningkatan Layanan Administrasi Kependudukan Melalui Identitas Kependudukan Digital (IKD) : Studi Kesiapan SDM dalam Era Transformasi Digital di Provinsi Riau - Syafitri, Indrian; Nurman, Nurman; Mardatillah, Annisa; Hefriyenni, Resti (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2025)
The Digital Population Identity (Identitas Kependudukan Digital/IKD) emerges as an innovation by the Ministry of Home Affairs of the Republic of Indonesia to strengthen data security, accelerate services, and improve bureaucratic effectiveness. This study aims to analyze the readiness of human resources (HR) in the implementation of IKD in Riau Province, with a focus on enhancing population administration services within the context of digital transformation. The research employed a descriptive qualitative approach with data collection techniques including in-depth interviews, direct observation, and document studies at the Department of Population and Civil Registration in several regencies/cities. Data were analyzed using reduction, presentation, and thematic interpretation techniques to provide a comprehensive picture of HR readiness in facing the digitalization of administrative services. The findings indicate that operational-level HR has a basic understanding of the benefits of IKD; however, limitations remain in digital competence, uneven availability of supporting infrastructure, and resistance from some segments of society in adopting new technologies. The study also highlights the potential for improvement through technical training programs, enhancement of digital literacy, and more intensive public socialization strategies. The novelty of this research lies in its emphasis on HR readiness as a strategic factor in the successful implementation of IKD at the regional level, particularly within the diverse geographical and social context of Riau Province. The implications of the study suggest the need for local government policies that support HR capacity development programs and equitable distribution of information technology infrastructure to ensure the optimal and sustainable implementation of IKD.